Chairing language and literature departments in the Philippines - Barredo, Tita Joy B. (Animo Repository, 2001)
Not many studies have been made in the area of chairing an academic department in the Philippines. Moreover, a study on managing the language and literature departments is something that has never been explored before. This dissertation makes use of management by culture and the western model of managing academic departments as the theoretical frameworks in addressing the questions raised in the statement of the problem.Twelve chairs heading the language and literature departments from different universities and colleges in the Philippines are interviewed to discover the existing paradigm from which their administrative styles are patterned. The author then take an in-depth look at their responses to determine the validity of the theoretical frameworks utilised in the study and if the chairs themselves offer new insights on how one can be a successful department head.The author has found out that although most chairs are not aware of the existence of the conceptual framework of management by culture, their being Filipinos has assisted them in dispensing their duties and responsibilities. In the final analysis, the study concluded that the better way to manage the language and literature departments in the Philippines is to take the first step and accept and undertake a pivotal change, that is, to separate the two disciplines. The recommendation the author make is that a model-building study will help present the future chairs of these departments manage their academic units better and with a keen sense of understanding of the idiosyncracies that go with the territory.